NOTIFICATION !!! - Papers, Conference (European Scientific Journal, ESJ, 2015)
The content of this ESJ special edition is an outcome of the conference â€œInternational Conference on tourism vs heritageâ€ which was held in February 2015 in Lisbon, Portugal. The papers have been reviewed by the conference committee.